The role of passive immunization in the age of SARS-CoV-2: An update - Fischer, Johannes C.; Zänker, Kurt; Van Griensven, Martijn; Schneider, Marion; Kindgen-Milles, Detlef; Knoefel, Wolfram Trudo; Lichtenberg, Artur; Tamaskovics, Balint; Djiepmo-Njanang, Freddy Joel; Budach, Wilfried; Corradini, Stefanie; Ganswindt, Ute; et al. (European Journal of Medical Research, 2020)
The rapid spread of the corona virus pandemic is an existential problem for many people in numerous countries. So far, there is no effective vaccine protection or proven therapy available against the SARS-CoV-2 virus. In this review, we describe the role of passive immunization in times of the corona virus. Passive immunization could be a bridging technology to improve the immune defense of critically ill patients until better approaches with effective medications are available.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Bridge therapy; Convalescent plasma; Covid-19; High risk; Immunology; Intensive care unit; Respiratory failure